Odpowiedź
[tex]\displaystyle{ \frac { \: 2 \cdot \sqrt{ 1,75 } \: } { \sqrt{ 7 } } - \frac { \: \sqrt{ 63 } \: } {\sqrt{ 7 } } = }\\\\\\\displaystyle{ \frac { \: 2 \cdot \sqrt{ \displaystyle{ \frac {7}{4} } } \: } { \sqrt{ 7 } } - \frac { \: \sqrt{ 9 \cdot 7 } \: } {\sqrt{ 7 } } = }\\\\\\\displaystyle{ \frac { \: \sqrt{ 4 } \cdot \sqrt{ \displaystyle{ \frac {7}{4} } } \: } { \sqrt{ 7 } } - \frac { \: \sqrt{ 9 } \cdot \sqrt{ 7 } \: } {\sqrt{ 7 } } = }\\\\\\[/tex]
[tex]\displaystyle{ \frac { \: \sqrt{ 7 } \: } { \sqrt{ 7 } } \: - \: \sqrt{ 9 } } = }\\\\\\\\1 \: - \: 3 \: = \boxed { \:\: -2 \:\: }[/tex]